Lvthers fore-rvnners, or, A clovd of witnesses deposing for the Protestant faith, gathered together in the historie of the Waldenses, who for divers hundred yeares before Luther successively opposed popery, professed the truth of the Gospell, and sealed it with their bloud : being most grieuously persecuted and many thousands of them martyred by the tyrannie of that man of sinne, and his superstitious adherents and cruell instruments. : Diuided into three parts: The first concernes their originall beginning ... : The second containes the historie of the Waldenses called Albigenses : The third concerneth the doctrine and discipline which hath bene common amongst them, and the confutation of the doctrine of their aduersaries. : All which hath bene faithfully collected out of the authors named in the page following the preface / by I.P.P.L. ; translated out of French by Samson Lennard. [electronic resource] :
Summary goes here